Risk misperceptions of structured financial products with worst-of payout characteristics revisited - Nobuyuki Hanaki (Osaka University, Institute of Social and Economic Research (ISER), 2021)
In this paper, we reexamine a bias revealed by Kunz et al. (2017) regarding structured financial products known as barrier reverse convertibles (BRCs) with worst-of payout characteristics. Namely, using a nonincentivized survey of investor risk perceptions, Kunz et al. (2017) found that when safe assets are included with risky assets to provide the underlying assets of a BRC, investors erroneously perceive a lower risk for the BRC when in fact it becomes higher. We confirm the same bias among student participants using the results of an incentivized experiment. However, we do not observe any similar bias among finance professionals.
Keywords: G11; G41; C99; 330; Experiment; Barrier Reverse Convertibles